Empowering Housewives Through Training in Making D'Bagur (Savory Pork Jerky) Increases Opportunities for Economic Prosperity - Achmadi, Puspita Cahya; Karlina, Maria Aprilliana Ade; Yohana Maria Febrizki Bollyn (Universitas Pendidikan Ganesha, 2024)
Seeing the problems experienced by many residents who own pigs but only sell them live and many residents, especially mothers, want to improve their economic welfare, Community Service activities are carried out. Pigs are livestock that are used for their meat. Pork is a source of animal protein. The nutritional content of 100 grams of fresh pork is 450 kcal, 11.9 grams of protein, 45 grams of fat. Looking at the pork content, the strategy used is to diversify pork into processed beef jerky. This initiative aims to encourage creative ideas and entrepreneurial motivation among housewives in Bangka Leda Village. This type of research is qualitative. The subjects involved in this research were housewives. Data collection methods. This community service activity includes observation, Focus Group Discussion (FGD), socialization, product manufacturing training assistance, discussion and evaluation. The data analysis method used is descriptive analysis. The results obtained from this Community Service activity were that housewives received a positive and very enthusiastic response. It is hoped that making creative and innovative products can increase the level of knowledge, skills and opportunities for economic prosperity. Implications of this research This training not only provides technical skills, but also opens up new business opportunities for housewives, who were previously not involved in productive economic activities.